Association of Dementia in Ischemic Stroke: A Case Control Study - Md Salahuddin, Abu Jafor; Khan, Md Rezaul Karim; Bhuiyan, Md Muniruzzaman; Md Eusuf, Nuruddin; Zahid, Rased Imam; Patwary, Khairul Kabir; Salahuddin, Muhammad; Hassan, Md Sayeed; Alim, Md Abdul; Majumder, Sukumar; Rana, Md Masud (Bangladesh Journal of Neuroscience, 2014)
Objectives: To evaluate the association of dementia in ischemic stroke. Methodology: This case control study was carried out in the department of Neurology at BSMMU, Dhaka from 1st January 2010 to 31st December 2011 for duration of two years to evaluate the association of dementia in ischemic stroke. The target population for this study include all patients presented with ischemic stroke at the range of 3 to 6 months after stroke with the age group of 40 to 70 years are included in this study and patients of dementia other than ischemic stroke like Alzhiemer’s disease, vit-B12 deficiency, thyroid dysfunction were excluded from this study. A total number of 120 respondents were included in this study. Age & sex matched 60 patients of ischemic stroke were selected as cases and rest 60 people were taken as control group. Informed written consent was taken from each patient or his/ her attendant. All information regarding history and physical findings; and other risk factors for dementia were collected to fill up the preformed questionnaire. Relevant physical examinations like nervous system examination, selected general and systemic examination were recorded. Result & Observation: Dementia was present in case and control group 18(30.0%) and 2(3.3%) respectively. The difference was statistically significant (p=0.001). Present smoking habit was more in case (45.0%) than in control group (16.7%) which was statistically significant (p=0.001) with a OR of 4.07 with a 95% CI of 1.89-8.75. Past smoking habit was more in case (16.7%) than control group (11.7%). Non-smoker was more in control (71.7%) than case group (38.3%). Diabetes mellitus was more common in case group (38.3%) than control group 5(8.3%) which was statistically significant (p=0.001) with a 6.84 OR and 95% CI of 2.39-19.6. Conclusion: The study permit to conclude that dementia is directly associated with ischemic stroke. We found a correlation between age, family history of dementia, hypertension, diabetes mellitus and dyslipidemia with dementia. Bangladesh Journal of Neuroscience 2014; Vol. 30 (1): 35-44